2017
DOI: 10.1097/brs.0000000000001954
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sirt1 Plays in Nucleus Pulposus Cells and Intervertebral Disc Degeneration

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…Our previous studies demonstrated that SIRT1 has a protective role in IVDD 31,32 . Furthermore, several studies revealed that SIRT1 plays a key role in mitophagy and apoptosis in a variety of aging-related diseases via SIRT1-Parkin-Mitohphagy pathway [33][34][35][36][37] .…”
Section: Discussionmentioning
confidence: 96%
“…Our previous studies demonstrated that SIRT1 has a protective role in IVDD 31,32 . Furthermore, several studies revealed that SIRT1 plays a key role in mitophagy and apoptosis in a variety of aging-related diseases via SIRT1-Parkin-Mitohphagy pathway [33][34][35][36][37] .…”
Section: Discussionmentioning
confidence: 96%
“…Accumulating evidence indicates that SIRT1 has an important role in IDD and osteoarthritis (OA) pathogenesis 32 40 . More recently, the pivotal role of SIRT1/NF-κB pathway in age-related diseases including IVD and bone has been recognized 41 47 .…”
Section: Discussionmentioning
confidence: 99%
“…NPMSc proliferation, stemness preservation and colony formation are decreased, whereas apoptosis is increased in individuals with Idd (22). Additionally, SIRT1 exerts a protective effect on Idd, and its expression is downregulated in the degenerating disc (23). Although multiple studies on Idd and SIRT1 or Idd and NPMScs have been conducted, only a few have focused on the interaction among these three factors, and even fewer have analyzed possible signaling pathways.…”
Section: Discussionmentioning
confidence: 99%